Limb Regeneration in Amphibians: Immunological Considerations - Anthony L. Mescher; Anton W. Neff (The Scientific World Journal)
We review key aspects of what is known about limb regeneration in urodele and anuran amphibians, with a focus on the early events of the process that lead to formation of the regeneration blastema. This includes the role of the nerves and wound epithelium, but also covers the inflammatory effects of the amputation trauma and their importance for regenerative growth. We propose that immunotolerance is important for limb regeneration and changes in its regulation may underlie the loss of regenerative capacity during anuran metamorphosis.